The acceptability of physical intimacy among heterosexual partners of Poblacion, Miag-ao, Iloilo - Dingcong, Razelyn Lim. (2003.)
The study deals with the acceptability of physical intimacy among heterosexual partners of Poblacion, Miagao. The objectives of the study are to determine whether the age, gender, length of relationship, and religion of the respondents influence their acceptability of physical intimacy., The pre-test was conducted in Southern Iloilo Polytechnic College. Two types of item analysis were used to get the reliability of the items from the Likert-type questionnaire namely, the Item Analysis Using the Easiness Method and the Item Analysis Using the Mean Differences. There were 20 respondents used for the pre-test. The final research had 32 respondents. Using the Mann-Whitney U test for the age and gender variables, it was found out that there is no significant relation in the respondents' age and their acceptability of physical intimacy. On the other hand, the gender of the respondents influence their acceptability of physical intimacy. Lastly, using the Kruskall-Wallis H test for the length of relationship and religion variables, it was found out that only the length of relationship had significant relation on the respondents' acceptability of physical intimacy. The religion on the other hand does not influence the respondents' acceptability of physical intimacy.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Heterosexual Partyners -- Miagao, Iloilo